Intrapersonal, interpersonal, and social outcomes of the social sharing of emotion. (February 2020) - Rimé, Bernard; Bouchat, Pierre; Paquot, Louise; Giglio, Laura
Abstract : Emotional experiences trigger the social sharing of emotion. This disclosure of emotional facts and feelings to the social surrounding was generally considered as a simple process of emotional release. The empirical data reviewed in this article invalidate this simplistic view. They show that the social sharing of emotions is a complex process that results not only in intrapersonal effects for the source person, but also in important interpersonal and social outcomes. The intrapersonal effects of the social sharing of emotions are varied, they do not necessarily go together, and they respond to specific conditions. At the interpersonal level, both the sharing of positive and negative emotional episodes affects relationships with the audience. Finally, the research highlights broader social effects relating to social structure, social norms, group action, beliefs, collective resilience, and intergroup relations.